Faktor dan Penanganan Kesulitan Membaca Siswa Kelas III Madrasah Ibtidaiyah Daarul Hikmah Tangerang - Efa Madani; Anjar Sulistyani; Dewi Utami (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
Reading ability is one of the most significant factors that facilitates pupils' comprehension and interpretation of the reading material. Beginning reading is an issue in elementary school, particularly in third grade, which marks the beginning of the higher class level. Reading issues can impede teaching and learning in schools, as much of the material has been acquired by the third grade. In addition, non-reading pupils have trouble compensating for learning activities with peers during teaching and learning activities. This study intends to identify the students of Class III MI Daarul Hikmah Tangerang who struggle with reading, as well as the variables that contribute to these students' reading challenges and the strategies used to assist those children. This study employs a descriptive qualitative methodology using a Case Study design. For strategies of data collecting, including interviews, tests, documentation, and observation. Six of twenty-four Class III MI Daarul Hikmah Tangerang students have reading difficulties, the delay factor in reading pupils is influenced by the absence of learning assistance from the family, speech abnormalities in children since childhood, and lack of motivation in learning among students. Teachers and parents play a crucial role in addressing kids' reading issues, specifically through rigorous tutoring activities outside of school hours, parental monitoring of children's play and learning hours at home, and the development of home and school-based learning motivation.Keywords: Reading Difficulty, Reading Difficulty Factor, Handling Abstrak Salah satu hal yang penting agar siswa mudah memahami dan memaknai isi bacaan adalah keterampilan membaca. Membaca permulaan menjadi salah satu permasalahan di sekolah dasar khususnya kelas 3 yang merupakan titik awal siswa untuk memasuki jenjang kelas atas. Kesulitan membaca dapat menghambat kegiatan belajar mengajar di sekolah, karena pada jenjang kelas 3 muatan materi sudah banyak didapatkan. Selain itu, siswa yang belum bisa membaca, kesulitan dalam mengimbangi kegiatan pembelajaran bersama temannya saat berlangsungnya kegiatan belajar mengajar. Penelitian ini bertujuan untuk mengetahui siswa kelas III MI Daarul Hikmah Tangerang yang mengalami kesulitan membaca, menganalisis faktor kesulitan membaca siswa kelas III MI Daarul Hikmah Tangerang, dan penanganan secara tepat untuk mengentaskan siswa yang mengalami kesulitan dalam membaca. Adapun Penelitian yang dilakukan ini menggunakan metode kualitatif deskriptif dengan pendekatan studi kasus. Untuk teknik pengumpulan data, berupa wawancara, tes, dokumentasi, dan observasi. Hasil penelitian yang ditemukan yaitu: terdapat 6 dari 24 siswa kelas III MI Daarul Hikmah Tangerang yang mengalami kesulitan membaca, faktor keterlambatan membaca siswa dipengaruhi oleh kurangnya dukungan belajar dari keluarga, gangguan bicara pada anak sejak kecil, dan kurangnya minat belajar pada siswa. Guru dan orangtua menjadi kunci dalam penanganan kesulitan membaca siswa, yaitu dengan kegiatan bimbingan belajar intensif di luar jam sekolah, pemantauan jam bermain dan belajar anak di rumah oleh orangtua, serta membangun motivasi belajar baik di rumah maupun sekolah.Kata Kunci: Kesulitan Membaca, Faktor Kesulitan Membaca, Penanganan